A Semiotic Approach to Translating between Arabic and English - Almanna, Ali; Farghal, Mohammed (Journal of Ecohumanism, 2024)
Drawing on Arabic authentic excerpts that feature key semiotic signs in English translation, this paper shows how challenging it is for translators to capture the communicative value of such signs. The discussion shows that signs have two important components: iconic and indexical. In a few cases in which a happy coincidence may exist in the language pair, the translator can relay both components and, optimally, capture the semiotics of the sign. However, in most contexts, he/she needs to search for other translation procedures. These may include formal equivalents that follow source language norms, functional equivalents that embrace target language iconicity, ideational equivalents that only capture the sign’s indexical import, or a combination of two procedures. In any case, the translator should pay utmost attention to the interpretant of the semiotic sign in its relevant context because the same sign may have to be rendered differently.